Die Vertextung von Termini als Ausweis textueller Strategien in technischen Textsorten - Kastberg, Peter (HERMES - Journal of Language and Communication in Business, 1999)
In this paper I argue that the textualization of terms in technical texts - be it as part of a procedural condensation or expansion - is determined by the author’s textual and text generic strategy in appreciation of the knowledge level and knowledge interest of his addressee rather than the technical matter conveyed in the text.